COALIFICATION TREND IN SOUTH SUMATERA BASIN - BINARKO SANTOSO; BUKIN DAULAY (Indonesian Mining Journal, 2006)
Similarities and differences in rank characteristics in the Bukit Asam coals within the South Sumatera Basin reflect their geological setting, particularly influence of the intrusion of andesite bodies and stratigraphic aspect. Rank variation was determined by vitrinite reflectance measurements of one hundred and thirty-four (134) coal samples. The higher vitrinite reflectance of the coals is a result of higher regional coalification level in the basin associated with the local and variable effects of igneous intrusions, as well as the greater cover/overburden. Philosophically, the higher the temperature, the more profound the alteration occurs; and the thicker the overburden, the more profound the rank occurs as well. The thermally affected coals have vitrinite reflectances between 0.69% (high volatile bituminous) and 2.60% (anthracite), whereas those of not affected are between 0.30% (brown coal) and 0.53% (sub-bituminous) according to the Australian classification.